Response of colonic motility to dopaminergic stimulation is subverted in rats with nigrostriatal lesion: relevance to gastrointestinal dysfunctions in Parkinson's disease. Issue 12 (3rd October 2015) - Levandis, G.; Balestra, B.; Siani, F.; Rizzo, V.; Ghezzi, C.; Ambrosi, G.; Cerri, S.; Bonizzi, A.; Vicini, R.; Vairetti, M.; Ferrigno, A.; Pastoris, O.; et al.
Abstract: Background: Constipation is extremely common in patients with Parkinson's disease (PD) and has been described in PD animal models. In this study, we investigated whether a PD‐like degeneration of dopaminergic neurons of the substantia nigra can influence peristalsis in colonic segments of rats by impacting on enteric dopaminergic transmission. Methods: Male, Sprague–Dawley rats received a unilateral injection of neurotoxin 6‐hydroxydopamine (6‐OHDA), or saline, into the medial‐forebrain‐bundle. Peristaltic activity was recorded in isolated colonic segments, in baseline conditions and following exposure to combinations of D2 receptor (DRD2) agonist sumanirole and antagonist L‐741626. Dopamine levels and DRD2 expression were assessed in the ileum and colon of animals. We also investigated the involvement of the dorsal motor nucleus of the vagus (DMV) — a potential relay station between central dopaminergic denervation and gastrointestinal (GI) dysfunction — by analyzing cytochrome c oxidase activity and FosB/DeltaFosB expression in DMV neurons. Key Results: We observed profound alterations in the response of colonic segments of 6‐OHDA lesioned animals to DRD2 stimulation. In fact, the inhibition of colonic peristalsis elicited by sumanirole in control rats was absent in 6‐OHDA‐lesioned animals. These animals also showed reduced DRD2 expression in the colon, along with elevation of dopamine levels. No significant changes were detected within the DMV. Conclusions & Inferences: Our results demonstrate that selective lesion of the nigrostriatal dopaminergic pathway subverts the physiological response of the colon to dopaminergic stimulation, opening new perspectives in the comprehension and treatment of GI dysfunctions associated with PD. Abstract : Rats bearing a 6‐OHDA induced lesion of the nigrostriatal tract show profound alterations in the response of colonic segments to dopaminergic D2 stimulation. In fact, the inhibition of colonic peristalsis elicited by D2 agonist sumanirole in control rats was absent in 6‐OHDA‐lesioned animals. These animals also showed reduced DRD2 expression in the colon, along with elevation of dopamine levels. Our results demonstrate that selective lesion of the nigrostriatal dopaminergic pathway subverts the physiological response of the colon to dopaminergic stimulation, opening new perspectives in the comprehension and treatment of GI dysfunctions associated with PD.